Land Fund Structure and Land Improvement Works in Galati County - Marius Daniel NICULA; Dumitrache Bogdan BRATOVEANU; Petre Adrian LIPTAC; Silvius STANCIU (Communications of International Proceedings, 2020)
There is great pressure on farmers worldwide to maximize their economic and social benefits from the land they own, while facing land degradation and desertification. Sustainable land management is the key answer to these challenges and is land management through which human society aims to improve agricultural production, living conditions and ecosystems. In order to integrate irrigation and drainage works in an integrated management of natural resources, it is necessary to establish a set of measures to coordinate and support the factors involved in this field, especially end users (farmers, organizations of water users for irrigation, specialists in the field of land improvements). The structure of agricultural land exploitation in Romania has not changed significantly during the last decade, maintaining the same fragmentation and the same extreme polarity, major impediments to increasing the competitiveness of the agricultural sector. Romania suffers from the most acute problem of fragmentation of agricultural property among all the countries of the European Union and has an average size of exploitation similar to Malta or Cyprus, island countries with much smaller agricultural areas than Romania. The use of agricultural land is determined by the overall evolution of human society, mainly by the demand-supply ratio of agricultural products that manifests itself on the market. The demand for agricultural products is determined by the needs of final consumer or industrial consumption. These needs are directly related to the number of population, its purchasing power and the degree of integration and development of agricultural raw materials processing industries. The supply of agricultural products is determined by the area in the agricultural circuit and the level of yields per hectare. The use of agricultural land is influenced by the agro-climatic conditions, as well as by the economic, financial, demographic, technical and technological conditions existing in a country at a given time. An analysis of the evolution of land use categories in Galati County shows that the agricultural area of Galati County is 351779 ha, of which 289581 ha of arable, 40914 ha of natural pastures, 700 ha of natural finesse, 19521 ha of vineyards and 1763 ha of orchards and fruit nurseries. Globally, the effects of desertification are increasingly being observed as a consequence of long periods of drought and the reduction of fertile areas that have led to a decrease in crop production. In Galati County, the phenomena of excessive drought affected large areas of agricultural land in 2015 and 2020. Irrigation facilities in Galati County represent 41.4% of the arable land of the county, of which 33,171 ha were rehabilitated, which represents 22.8 % of the arranged surface and 9.4% of the arable surface of Galati County.
Keywords: Land Fund; Land Improvements; Irrigation